Quality of life among hospitalized geriatric patients in medical ward Hospital Universiti Sains Malaysia (HUSM) Kubang Kerian Kelantan - Lian, Dora Liu Ha (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Quality of Life (QoL) is unique in different individuals. The measurement of QoL among the geriatric patients can assist health professionals in achieving clinical objectives which included assessing the effects of illness and treatment, identifying the need of support services and developing health enhance environment. Objective of this study was to assess the QoL among hospitalized geriatric patients in Medical Ward Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan. A cross-sectional study was conducted among geriatric patients who were admitted to Medical Ward HUSM with any diagnosis. There were 51 respondents participated in this study. Data was collected using self-administerd questionnaire (WHOQOLBREF) with enquiring and explaining about the existence of phenomena understudy by the researcher. Overall finding of the study revealed that majority of the independent variables, demographic data are not significant with the dependent variables, QoL of the hospitalized geriatric patients. Among all the study variables, QoL of the respondents were not associated with age, race, marital status and financial sources. However, there is an association between educational level and satisfaction with health status among the respondents. In addition, the mean different of physical health and psychological health among gender of respondents also showed significantly different. Finding showed QoL m male respondents were higher than female respondents in all aspects. As a conclusion, QoL of the geriatric patients will not decline just because of ageing and there is a significantly different between male and female's QoL. Hence, the health care providers should be cautious before making any assumptions about the QoL of individual patients and just not merely based on their health status.